2016
DOI: 10.1155/2016/2592319
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Mild Stress Modulates Activity-Dependent Transcription of BDNF in Rat Hippocampal Slices

Abstract: Although activity-dependent transcription represents a crucial mechanism for long-lasting experience-dependent changes in the hippocampus, limited data exist on its contribution to pathological conditions. We aim to investigate the influence of chronic stress on the activity-dependent transcription of brain-derived neurotrophic factor (BDNF). The ex vivo methodology of acute stimulation of hippocampal slices obtained from rats exposed to chronic mild stress (CMS) was used to evaluate whether the adverse experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…This interplay is aimed to protect the body from immune system dysregulation and minimize tissue damage from associative systemic inflammation [7] , [8] , [10] , [11] . Chronic activation of the HPA axis affects the release of glucocorticoids and contributes to immune dysfunction as immune response is signified by glucocorticoid release [7] , [12] , [13] , [14] , [15] .…”
Section: Support For Hypothesismentioning
confidence: 99%
“…This interplay is aimed to protect the body from immune system dysregulation and minimize tissue damage from associative systemic inflammation [7] , [8] , [10] , [11] . Chronic activation of the HPA axis affects the release of glucocorticoids and contributes to immune dysfunction as immune response is signified by glucocorticoid release [7] , [12] , [13] , [14] , [15] .…”
Section: Support For Hypothesismentioning
confidence: 99%
“…We have previously shown that CMS is able to induce depressive-like behaviors such as anhedonia (Rossetti et al, 2016) as well as cognitive impairment (Calabrese et al, 2017), which are associated with alterations in key molecular players for psychiatric disorders (Luoni et al, 2014; Calabrese et al, 2016b; Molteni et al, 2016). We also investigated the effect of a chronic treatment with lurasidone in counteracting the CMS-induced alterations in rat hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamatergic synapses that lack AMPAR current― known as “silent synapses”―are not able to achieve sufficient depolarization (excitation) despite containing functional N-methyl-D-aspartate (NMDA) receptors 27 . In addition to NMDA receptor-dependent Ca2+ influx, AMPAR-dependent synaptic Ca2+ influx is required for NMDA receptor-mediated LTP 14 - 15 , 28 . Additionally, enhanced LTP expression has been observed in mice with genetic deletion of GluR2 29 , 30 .…”
Section: The Role Of the Ampar In Synaptic Plasticitymentioning
confidence: 99%
“…Chronic stress-induced abnormalities in synaptic plasticity are modulated by corticosterone, neurotrophins, oxidative stress, and various neurotransmitters 8 , 11 , 12 , 13 . For example, chronic mild stress has been shown to reduce hippocampal transcription of hippocampal brain-derived natriuretic factor (BDNF), which reached basal levels in an isoform-specific manner by KCl-treated depolarization, suggesting that neurotrophins differentially regulate activity-dependent transcription of BDNF 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation